Teacher Training, Educational Materials Usage, and Learning: Models of Educational Material Provision in Peru - Eguren, Mariana (2013)
Educational materials (textbooks in particular) are key for improving learning, especially in precarious school contexts. In the case of Peru, from 1990 on, the State has experimented with different models of educational material provision. In spite of their differences, they share a lack of impact in improving students’learning outcomes. The authors state that the problem stems from the absence of teacher training in how to use educational materials, which should be a core element of any model of educational material provision.